A Joint Suppression Method of Scalloping and Inter-Scan Banding for SAR Images - Xinwei An; Wei Yang; Haijun Shen; Hongcheng Zeng; Fei Zou; Jiadong Deng; Can Su; Wei Liu (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
Due to a wide swath at the order of hundreds of kilometres, interscan banding (ISB) may occur in both ScanSAR and TOPS modes of a synthetic aperture radar (SAR), leading to degraded image quality. In this aticle, the causes of ISB are analyzed and an ISB suppression method based on Retinex theory and global weighting is proposed. First, the image with ISB is considered as an image with uneven lighting, and ISB is considered as a lighting component. The ISB component is calculated using a global weighting method. Based on previous studies, the coupling relationship between ISB and scalloping (another issue commonly found in ScanSAR) is identified, and a joint procedure for suppressing ISB and scalloping is established. The proposed method is a post-processing technique that does not require any other additional information, such as the noise equivalent sigma zero. Experimental results based on real SAR images from Gaofen-3 and Sentinel-1 indicate that the proposed method can significantly reduce the effect of ISB and improve the image quality, and it is more efficient and robust compared to existing methods.